2002
DOI: 10.1128/jvi.76.2.541-551.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cloned Genomic DNA of Type 2 Porcine Circovirus Is Infectious When Injected Directly into the Liver and Lymph Nodes of Pigs: Characterization of Clinical Disease, Virus Distribution, and Pathologic Lesions

Abstract: Infection of animals with a molecular viral clone is critical to study the genetic determinants of viral replication and virulence in the host. Type 2 porcine circovirus (PCV2) has been incriminated as the cause of postweaning multisystemic wasting syndrome (PMWS), an emerging disease in pigs. We report here for the first time the construction and use of an infectious molecular DNA clone of PCV2 to characterize the disease and pathologic lesions associated with PCV2 infection by direct in vivo transfection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
203
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(209 citation statements)
references
References 56 publications
(98 reference statements)
3
203
1
2
Order By: Relevance
“…As a result, the authors confirmed that although PCV2 was the agent associated with PMWS, cofactors are crucial for the development of severe clinical PMWS. The infectiousness of another PCV2 DNA clone was checked by intramuscular and intraperitoneal injections [32] with similar results [14]. Since no clinical PMWS was reproduced with this pure PCV2 inoculum, the purpose of our work was to evaluate the impact of immunostimulation on the PMWS severity level showed by six-week-old specific-pathogen-free piglets after injection of pure tandem-cloned PCV2 DNA by the intramuscular route.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…As a result, the authors confirmed that although PCV2 was the agent associated with PMWS, cofactors are crucial for the development of severe clinical PMWS. The infectiousness of another PCV2 DNA clone was checked by intramuscular and intraperitoneal injections [32] with similar results [14]. Since no clinical PMWS was reproduced with this pure PCV2 inoculum, the purpose of our work was to evaluate the impact of immunostimulation on the PMWS severity level showed by six-week-old specific-pathogen-free piglets after injection of pure tandem-cloned PCV2 DNA by the intramuscular route.…”
Section: Introductionmentioning
confidence: 80%
“…AF201311) was cloned in tandem in pBluescript KS+ (Stratagene, La Jolla, CA, USA) at the SacI site as described by Fenaux et al [14]. DNA was produced at a concentration of 0.8 mg/mL without lipopolysaccharides (0.046 endotoxin unit/µg) by PlasmidFactory (Bielefeld, Germany).…”
Section: Production Of Tandem-cloned Pcv2 Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, both groups of swine expressed the full spectrum of host-virus interactions (asymptomatic infection to overt PMWS), gross lesions, and characteristic histologic lesions now attributable to PCV-2 infection and identified in commercial swine production operations. 1,7,13,31,32,34,35,37 All experimental pigs were euthanized when moribund or at 4-5 weeks of age regardless of disease status. Disease status, for the swine still alive at the end of the experiment was determined ultimately by a combination of clinical presentation, gross lesions, and tissue virus burden as determined by IHC and quantitative virus recovery.…”
Section: Figurementioning
confidence: 99%
“…FR823451) was isolated from a pig spleen and propagated in PK15 cells. Tandem dimers of the PCV2 genome and PCV2 mutant were constructed and used to infect PK15 cells (Fenaux et al, 2002;Liu et al, 2005). Primer sequences used for the PCR are described in Table S1 (available in the online Supplementary Material).…”
Section: Methodsmentioning
confidence: 99%